Synthesis and Characterization of New Imines-Imides Functionalized Compounds Derived from Trimethoprim moiety Supplemented with Aminothiazole - Mohammad F. Mesher Al-Dulaymmi (Journal of Global Pharma Technology, 2019)
Imides, Imines, five- and six- membered heterocyclic rings are among the compounds that have attracted a considerable attention of work due to their versatile biological activities. Therefore including these functional in the same compound perhaps enhancing the whole activity of the synthesized compounds. Trimethoprim moiety which is antibacterial drug possessing a pyrimidine ring and diamine groups, was selected as a starting material for this purpose. Mono imides (B1-B5) were prepared by treatment of the corresponding amic acids (A1-A5) (obtained by the reaction of equimolar amount of selected anhydrides and trimethoprim), with a suitable dehydrating agents. The remaining amino group was converted to the aminothiazole via the ring closure of the corresponding acetyl chloride amides (C1-C5) with thiourea in refluxing DMF. The target new imines (D1-D5) were synthesized by reaction of certain aldehydes and ketones with the new thiazoleamines. The structures of all the synthesized compounds were elucidated by considering the data of the FTIR, 1H-NMR, and other physical properties.Keywords: Trimethoprim, Imines, Imides, Cyclic anhydrides.